The Improvements of the Upper Zonal Currents by SST Assimilation Over the Tropical Pacific in a Coupled Climate Model - Sun, Zhikuo; Gao, Xin; Jin, Jiangbo; He, Juanxiong; Zheng, Fei; Zhang, He; Dong, Xiao; Zeng, Qingcun (Frontiers in Earth Science, 2022)
The upper zonal oceanic circulations in the tropical Pacific play a crucial role in modulating weather and climate in the tropical Pacific Ocean. However, they are poorly simulated in state-of-the-art climate models. We apply a simple bias correction scheme by only assimilating observed sea surface temperature (SST) data into a coupled earth system model, named the Chinese Academy of Sciences Earth System Model version 2 (CAS-ESM 2.0), to better reproduce the upper zonal currents in tropical oceans. There are mainly two reasons for this usage of SST assimilating method: 1) SST has dominant effects on the air–sea interactions over the tropical region; 2) The lack of effective and long-term ocean-current observation data currently. Our results show that the SST assimilation can significantly improve the strength of the Pacific Equatorial Undercurrent (EUC), the North Equatorial Countercurrent (NECC) and the South Equatorial Current (SEC) through reducing biases in the air–sea turbulence flux. Nevertheless, the SST assimilation has limited effects on improving the simulation of the spatial structure of these zonal currents in the tropical Pacific. The improvement of the wind stress curl over the tropical Pacific region mainly contributes to the improved simulated strength of the Pacific EUC, the NECC and the SEC. It also connects to the reduced biases in atmospheric convective precipitation and sea-level pressure induced by the reduction of the SST bias.